2008
DOI: 10.1159/000121607
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Ventricular Repolarization Duration and RR Interval in Normal Subjects and Patients with Myocardial Infarction

Abstract: Objectives: When either ventricular myocardium becomes ischemic or autonomic nervous system activity changes with age, the relationship between ventricular repolarization duration and RR interval will change as well. We studied the relationship between ventricular repolarization duration and RR interval among normal subjects in different age groups and between patients with myocardial infarction (MI) and age-matched healthy subjects. Methods: Ventricular repolarization duration variability (RDV) spectra were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Elevated beat-to-beat variability in ventricular repolarization duration, measured as changes in QT interval [QT variability (QTV)] on body surface ECG has been attributed to increased sympathetic outflow to the ventricles (32,46). Although it is widely believed that QTV is predominantly driven by heart period (RR interval) variability (RRV) under normal conditions during rest (34), several studies across a range of condi-tions, including healthy subjects (2), patients post-myocardial infarction (50), heart failure patients (25), and patients with diabetes mellitus (39), showed that a large part of QTV could not be solely attributed to RRV. An increased decoupling between RRV and repolarization variability was reported in healthy subjects following head-up tilt, a maneuver well known to increase sympathetic nerve activity (12), and QTV unrelated to RR and respiration (35) was shown to increase under similar experimental conditions.…”
mentioning
confidence: 99%
“…Elevated beat-to-beat variability in ventricular repolarization duration, measured as changes in QT interval [QT variability (QTV)] on body surface ECG has been attributed to increased sympathetic outflow to the ventricles (32,46). Although it is widely believed that QTV is predominantly driven by heart period (RR interval) variability (RRV) under normal conditions during rest (34), several studies across a range of condi-tions, including healthy subjects (2), patients post-myocardial infarction (50), heart failure patients (25), and patients with diabetes mellitus (39), showed that a large part of QTV could not be solely attributed to RRV. An increased decoupling between RRV and repolarization variability was reported in healthy subjects following head-up tilt, a maneuver well known to increase sympathetic nerve activity (12), and QTV unrelated to RR and respiration (35) was shown to increase under similar experimental conditions.…”
mentioning
confidence: 99%
“…This attenuation of the QT-RR relationship has also been found in MI patients with reduced LVEF when compared to those with coronary artery disease but no MI (Sosnowski et al, 2002). Others found no difference in the RR dependent component of QTV when comparing MI patients to healthy subjects (Lombardi et al, 1998;Zhu et al, 2008). These aggregate results suggest that the attenuation in QT-RR relationship is only prevalent in high-risk patients rather than in all patients post MI.…”
Section: Discussionmentioning
confidence: 64%
“…While they inevitably lost some of the repolarization time that might be an important indicator of ischemic myocardium with the longest repolarization delay, these spectral measures are likely to be helpful in the evaluation of areas of infarction in patients with MI. In the study by Zhu et al [1] , HRD significantly decreased with age in healthy individuals, but in MI patients, HRI significantly increased compared to agematched controls.…”
mentioning
confidence: 86%
“…Separating the autonomic component from the tissue component of repolarization variability is a contribution made by Zhu et al [1] . Perhaps future studies assessing outcome in patients with cardiomyopathies using these techniques will further advance our understanding of repolarization variability and help to prognosticate the risk for a poor outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation